Investigation of Colorimetric Properties of Woolen Yarn Dyed with Rheum Ribes Plant Root Extract - KOYUNCU, MENDERES (Asian Journal of Chemistry, 2010)
The dyeing of wool yarn using Rheum ribes roots as natural dye has been studied in conventional method. The effects of dyeing show higher colour strength values obtained by the latter. Dyeing with Rheum ribes roots has been shown to give good dyeing results. The results of washing fastness properties of the dyed wool yarn were fair to good. CIELAB values have also been evaluated and discussed.